AUTOMATION OF SERVERLESS APPLICATION DEPLOYMENT USING IAC: CASE OF ’AGRO MONITOR’ - Bulhakova, O. F.; Kostenko, V. V.; Bulhakov, D. S. (Systems and Technologies, 2025)
The article presents the results of research and practical implementation of serverless application deployment automation based on the Infrastructure as Code (IaC) concept. The primary focus is placed on analyzing modern tools and technologies that enable automated infrastructure management in cloud environments, as well as the deployment of serverless applications using IaC in a real-world project. The first part of the article examines the theoretical foundations of serverless architecture, which allows companies to reduce infrastructure maintenance costs, ensure automatic scaling, and pay only for the actual use of computing resources. The advantages and challenges of adopting the serverless approach are analyzed, including component interaction issues, version control, integration complexity, and security concerns. Particular attention is given to Function-as-a-Service (FaaS) platforms such as AWS Lambda, Azure Functions, Google Cloud Functions, and OpenFaaS. The article thoroughly investigates the role of Infrastructure as Code in the context of automating the deployment of serverless solutions. Two primary approaches to infrastructure description are considered-declarative declarative (Terraform, AWS CloudFormation) and imperative (Pulumi), and configuration-management tools (Ansible) – with an overview of their characteristics, benefits, and limitations. The key advantages of IaC for ensuring standardization, infrastructure reproducibility, CI/CD process integration, version control, and enhanced system security are highlighted. The practical section of the article focuses on the deployment automation of the «Agro Monitor» system, which is built on serverless architecture in the Microsoft Azure cloud environment. The Pulumi tool, which enables infrastructure definition using programming languages and provides flexibility in creating complex infrastructure scenarios, is applied. The system architecture, key components, API-based interaction mechanisms, as well as processes for automatic scaling, data processing, and report generation are described in detail. It is demonstrated that the proposed approach enables rapid deployment of new environments, reduces maintenance costs, enhances system stability, and improves scalability. The results confirm the effectiveness of combining serverless architecture and Infrastructure as Code for developing modern information systems characterized by high flexibility, stability, and economic feasibility. The developed solution can be beneficial for enterprises in various industries seeking to optimize infrastructure and accelerate the deployment of innovative IT products.